Discovery of selective urokinase plasminogen activator (uPA) inhibitors as a potential treatment for multiple sclerosis. Issue 20 (1st November 2018) - Islam, Imadul; Yuan, Shendong; West, Christopher W.; Adler, Marc; Bothe, Ulrich; Bryant, Judi; Chang, Zheng; Chu, Kieu; Emayan, Kumar; Gualtieri, Giovanna; Ho, Elena; Light, David; et al.
Graphical abstract: Highlights: Design and synthesis of benzylamine based selective and orally available inhibitors of uPA has been described. Prior knowledge of SAR has been used to optimize the lead compounds. Structure based drug design and modeling afforded analogs with acceptable drug like properties. Compound 824859 shows efficacy in acute and chronic EAE model for multiple sclerosis. This may represents new therapeutic strategy to treat MS using small molecule uPA inhibitors. Abstract: We report here the design and synthesis of a novel series of benzylamines that are potent and selective inhibitors of uPA with promising oral availability in rat. Further evaluation of one representative (ZK824859) of the new structural class showed that this compound lowered clinical scores when dosed in either acute or chronic mouse EAE models, suggesting that uPA inhibitors of this type could be useful for the treatment of multiple sclerosis.